(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The article talks about the important aspects of problem-based learning technologies in today’s modern educational conditions and the role of problem-based learning technologies in activating students’ learning and developing analytical, independent and creative thinking. Today’s modern education considers problematic processes that meet the requirements of scientific and technical development of young people with strong potential, competitive, special abilities, keeping up with the times, purposeful.